2010
DOI: 10.1016/j.ygcen.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and leptin receptor genes in Atlantic salmon: Cloning, phylogeny, tissue distribution and expression correlated to long-term feeding status

Abstract: The present study reports the complete coding sequences for two paralogues for leptin (sLepA1 and sLepA2) and leptin receptor (sLepR) in Atlantic salmon. The deduced 171-amino acid (aa) sequence of sLepA1 and 175 aa sequence for sLepA2 shows 71.6% identity to each other and clusters phylogenetically with teleost Lep type A, with 22.4% and 24.1% identity to human Lep. Both sLep proteins are predicted to consist of four helixes showing strong conservation of tertiary structure with other vertebrates. The highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
119
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 171 publications
(205 reference statements)
13
119
1
Order By: Relevance
“…The well-characterized key role of mammalian leptin in the control of energy homeostasis appears to be only partially shared with leptins in non-mammalian vertebrates (Volkoff 2006, Ronnestad et al 2010. Leptin and LEPR in evolutionarily early vertebrates show relatively low sequence similarity as compared with their mammalian orthologs.…”
Section: Discussionmentioning
confidence: 99%
“…The well-characterized key role of mammalian leptin in the control of energy homeostasis appears to be only partially shared with leptins in non-mammalian vertebrates (Volkoff 2006, Ronnestad et al 2010. Leptin and LEPR in evolutionarily early vertebrates show relatively low sequence similarity as compared with their mammalian orthologs.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term fasting in the anadromous Arctic charr is associated with downregulation of metabolic enzyme activity and upregulation of leptin A1 and SOCS expression in the liver also supported by the presence of the Lep receptor (LepR) gene in this organ in several fish species Rønnestad et al, 2010;Tinoco et al, 2012;Trombley et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…Mean ± s.e.m. hepatosomatic index (HSI; %), liver glycogen concentrations (µmolg been reported in Atlantic salmon (Rønnestad et al, 2010;Trombley et al, 2012), whereas a reduced liver Lep expression with fasting has been reported in goldfish (Carassius auratus) (Tinoco et al, 2012) and striped bass (Morone saxatilis) (Won et al, 2012), and no change with prolonged fasting in common carp (Cyprinus carpio) (Huising et al, 2006). The reason for these differences is not known, but they could relate to the degree of emaciation of the fish used in the different experiments, and interspecific differences in metabolic responses to an imposed fast.…”
Section: A Role Of Leptin In Liver Metabolism?mentioning
confidence: 99%
See 1 more Smart Citation
“…The first leptin-like gene was identified in the pufferfish (Takifugu rubripes) using syntenic gene analysis (Kurokawa et al, 2005). Leptin genes have subsequently been cloned from other teleost species, including common carp (Cyprinus carpio) (Huising et al, 2006), zebrafish (Danio rerio) (Gorissen et al, 2009), medaka (Oryzias latipes) (Kurokawa and Murashita, 2009), grass carp (Ctenopharyngodon idella) (Li et al, 2010), rainbow trout (Oncorhynchus mykiss) (Murashita et al, 2008), Atlantic salmon (Salmo salar) (Rønnestad et al, 2010;Angotzi et al, 2013), yellow catfish (Pelteobagrus fulvidraco) (Gong et al, 2013), orange-spotted grouper (Epinephelus coioides) , and Jian carp (Cyprinus carpio var. Jian) (Tang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%